Fall, recovery, and characterization of the Novato L6 chondrite breccia. (7th August 2014) - Jenniskens, Peter; Rubin, Alan E.; Yin, Qing‐Zhu; Sears, Derek W. G.; Sandford, Scott A.; Zolensky, Michael E.; Krot, Alexander N.; Blair, Leigh; Kane, Darci; Utas, Jason; Verish, Robert; Friedrich, Jon M.; et al.
Abstract The Novato L6 chondrite fragmental breccia fell in California on 17 October 2012, and was recovered after the Cameras for Allsky Meteor Surveillance (CAMS) project determined the meteor's trajectory between 95 and 46 km altitude. The final fragmentation from 42 to 22 km altitude was exceptionally well documented by digital photographs. The first sample was recovered before rain hit the area. First results from a consortium study of the meteorite's characterization, cosmogenic and radiogenic nuclides, origin, and conditions of the fall are presented. Some meteorites did not retain fusion crust and show evidence of spallation. Before entry, the meteoroid was 35 ± 5 cm in diameter (mass 80 ± 35 kg) with a cosmic‐ray exposure age of 9 ± 1 Ma, if it had a one‐stage exposure history. A two‐stage exposure history is more likely, with lower shielding in the last few Ma. Thermoluminescence data suggest a collision event within the last ∼0.1 Ma. Novato probably belonged to the class of shocked L chondrites that have a common shock age of 470 Ma, based on the U, Th‐He age of 420 ± 220 Ma. The measured orbits of Novato, Jesenice, and Innisfree are consistent with a proposed origin of these shocked L chondrites in the Gefion asteroid family, perhaps directly via the 5:2 mean‐motion resonance with Jupiter. Novato experienced a stronger compaction than did other L6 chondrites of shock‐stage S4. Despite this, a freshly broken surface shows a wide range of organic compounds.